2015
DOI: 10.3389/fmicb.2015.01007
|View full text |Cite
|
Sign up to set email alerts
|

New process for production of fermented black table olives using selected autochthonous microbial resources

Abstract: Table olives represent one important fermented product in Europe and, in the world, their demand is constantly increasing. At the present time, no systems are available to control black table olives spontaneous fermentation by the Greek method. During this study, a new protocol for the production of black table olives belonging to two Italian (Cellina di Nardò and Leccino) and two Greek (Kalamàta and Conservolea) cultivars has been developed: for each table olive cultivar, starter-driven fermentations were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 54 publications
8
59
1
Order By: Relevance
“…Nevertheless, yeast growth is not considered to present any consumption risk during the fermentation of green olives; On the contrary, yeast can metabolize ingredients that enrich the sensory palette and determine the quality of the final product [36]. It is worth noticing that the presence of yeasts, especially in the first days of the process, might have led to the enhancement of the starter culture in inoculated treatments due to their potential production of vitamins and other nutrients, which are mandatory for LAB growth [37].…”
Section: Physicochemical Analysesmentioning
confidence: 99%
“…Nevertheless, yeast growth is not considered to present any consumption risk during the fermentation of green olives; On the contrary, yeast can metabolize ingredients that enrich the sensory palette and determine the quality of the final product [36]. It is worth noticing that the presence of yeasts, especially in the first days of the process, might have led to the enhancement of the starter culture in inoculated treatments due to their potential production of vitamins and other nutrients, which are mandatory for LAB growth [37].…”
Section: Physicochemical Analysesmentioning
confidence: 99%
“…The proportions of these two genera then diminished to background levels within the first 70 days of the experiment. Thus far, few published reports have investigated the effects of exogenous yeast cultures on the population microbial dynamics and diversity in olive fermentations (5, 7, 16). According to culture-dependent methods applied in those reports, levels of the inoculated yeast cells were either maintained (5) or significantly reduced (16) as the fermentations progressed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, few published reports have investigated the effects of exogenous yeast cultures on the population microbial dynamics and diversity in olive fermentations (5, 7, 16). According to culture-dependent methods applied in those reports, levels of the inoculated yeast cells were either maintained (5) or significantly reduced (16) as the fermentations progressed. Such variation might be the result of the processing method applied or yeast strain- or species-dependent differences in the capacity to successfully invade and colonize olive drupes in the presence of the indigenous fermentation-associated microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most studied species for their potential use as starters in table olive production are LAB and yeasts. According to a recent study [31], the use of autochthonous yeasts and LAB has shown to shorten the time of fermentation, standardize the process, and improve their organoleptic and nutritional properties. Specifically, the role of microbial starters, selected for specific biotechnological and safety traits is considered to be the [31]:

improvement of table olives sensory attributes;

control of the fermentation process;

monitoring of the correct evolution of the process;

maintenance and/or improvement of nutritional and healthy features of the product;

protection from undesirable spoilage and pathogenic microorganisms;

fortification of table olives with microorganisms exhibiting probiotic potential;

enhancement of product stability and extension of shelf life.

…”
Section: Microbiology Of Table Olives Fermentationmentioning
confidence: 99%